Field notes contributed by Peter Ernzen, fall 1996 - Ernzen, Peteret al (1996)
List of birds and locations contributed by Peter Ernzen. Included with the field report is a note from Peter Ernzen to Thomas H. Kent regarding the unusual dates of several species observations. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed